IDENTITAS BUDAYA LOMBOK DALAM PUISI INDONESIA - Soleh, Dwi Rohman; Satrya HD, Dharma -; Suharto, V. Teguh (Adabiyyāt: Jurnal Bahasa dan Sastra, 2024)
This article aims to explain the construction of Lombok's cultural identity in three Indonesian poems. Cultural identity is considered a continuous production. In that approach, identity is a construct. Identity is constructed through language. Language is understood as a sign system. Therefore, the analysis of poetry uses sign analysis and semiotic analysis. In this analysis, signs can only be understood in the context of Lombok culture, in the context of the conceptual map of Indonesian society in Lombok. Signs can only be found in the cultural context of Lombok. The data were gathered from three different Lombok poems. The research result shows that in Perang Gurantang poems, Lombok cultural identity is different from Bali's cultural identity. Moreover, Di Gili Tak Ada yang Mengenal Pagi and Kemidi Rudat poems reveal hybrid cultural identity. Finally, Lombok cultural identity has a multicultural identity that gives respect to the differences between Lombok and Bali cultures. The acceptance of West and Malay-Islam culture forms Lombok cultural identity.